Aqueous Extract of Solanum nigrum Leaf Activates Autophagic Cell Death and Enhances Docetaxel-Induced Cytotoxicity in Human Endometrial Carcinoma Cells. (8th November 2012) - Tai, Cheng-Jeng; Wang, Chien-Kai; Chang, Yu-Jia; Lin, Chi-Shian; Tai, Chen-Jei
Abstract : Chemotherapy is the main approach in dealing with advanced and recurrent endometrial cancer. An effective complementary ingredient can be helpful in improving the clinical outcome. Aqueous extract of Solanum nigrum leaf (AE-SN) is a principal ingredient for treating cancer patients in traditional Chinese medicinal practice but lacks sufficient evidence to verify its tumor suppression efficacy. This study evaluated the antitumor effects of AE-SN and also assessed the synergistic effects of AE-SN with docetaxel On the human endometrial cancer cell lines, HEC1A, HEC1B, and KLE. The activation of apoptotic markers, caspase-3 and poly-ADP-ribose polymerase, and autophagic marker, microtubule-associated protein 1 light chain 3 A/B, wAS determined to clarify the cell death pathways responsible for AE-SN induced tumor cell death. Results indicated that AE-SN-treatment has significant cytotoxicity on the tested endometrial cancer cells with accumulation of LC3 A/B II and demonstrated a synergistic effect of AE-SN and docetaxel in HEC1A and HEC1B cells, but not KLE cells. In conclusion, AE-SN treatment was effective in suppressing endometrial cancer cells via the autophagic pathway and was also capable of enhancing the cytotoxicity of docetaxel in human endometrial cancer cells. Our results provide meaningful evidence for integrative cancer therapy in the future.